If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -1x) = 15 (1 * 3 + -1x * 3) = 15 (3 + -3x) = 15 Solving 3 + -3x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -3x = 15 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = 15 + -3 -3x = 15 + -3 Combine like terms: 15 + -3 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| (x+1)(x-2)=3 | | 1/3x2/11 | | 8/15=40/45 | | (6x+8)/(x+7) | | -7+(-6)= | | -390x+x^2+45000=0 | | 5(x-7)=-3x-27 | | X^3+.5x^2-10.5x-561=0 | | 7n-4n+10=5n-4 | | 7+f=19 | | -4(v-5)=0 | | -3x^2-180=0 | | 190=2w^2-1w | | -2x+6x+1=0 | | (5/(2x+3))+(4/(2x-3))=((14x+3)/(4x^2-9)) | | -12+6+0=0 | | 5t-7=4t | | 6b-5/8b-3b-4/6b | | f(x)=(x^2)(1-8x) | | 4x+7=62 | | y=r+2y-g | | P+14=18 | | -170=-10v | | 12+f=20 | | 8x+3x-2x-5=13 | | 15m=240 | | 2g=3b | | 15=4x-27 | | 266=-14b | | -(n+4)=5 | | -2x+12-3x=-6x-10 | | (x^3-x^2-62x+80)/(x+8) |